Der Tod Gottes und die Wissenschaft: Zur Wissenschaftskritik Nietzsches - Gentili, C.; Nielsen, Cathrin (Berlin De Gruyter, 2010)
With his talk of the "death of God", the philosopher Friedrich Nietzsche presented a diagnosis of the future that is both problematic and highly topical. Although this had been the subject of exhaustive discussion in connection with the resulting practical problem of the loss of values, its relevance for the status and selfunderstanding of the theoretical sciences has not been broached. 17 contributions from well-known scholars approach the subject by highlighting the connection between the specific nature of modern science and the non-involvement of theology.
Keywords: Nietzsche, Friedrich Wilhelm -- 1844-1900; Philosophy; Science; Theology